Instructors’ Perceptions and Experiences Re: Creating and Implementing Customized E-Texts in Education Courses - Deepak Prem Subramony (Educational Considerations, 2018)
This article presents partial findings from a case study exploring the outcome of an open alternative electronic textbook initiative launched by the College of Education at a large Midwestern university. On the basis of interview data generated by the aforesaid study, this article details the perceptions and experiences of instructors participating in the initiative regarding: (a) their rationale/justification for creating tailored/customized e-texts for their respective courses; (b) the strategies they followed, the challenges they faced, and the benefits they accrued as part of the process of designing, developing, and implementing these e-texts; and (c) how their students responded to the e-texts they created.